2019
DOI: 10.1149/2.0731910jes
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Fast Charge Challenges for Lithium-Ion Battery: Variability and Positive Electrode Issues

Abstract: Enabling a 10 min fast charge for electric vehicles is a possible route to reduce range anxiety and increase the utility of electric vehicles. While lithium plating during fast charging is a known challenge, the full suite of limitations which occur in full cells during a 10 min fast charge are unknown. In the present work the central constraints of extreme fast charging are explored through extensive experiments and analysis in single layer graphite/NMC532 pouch cells. Methods of developing fast-charging prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 47 publications
5
121
0
Order By: Relevance
“…Most of the capacity fade at the 8-C rate occurred before eight cycles; after that, there was only a slight additional fade. With cycling, the variability in the measured values of capacity tended to increase in a manner consistent with that reported by Tanim et al [55] By contrast, the variability in the 8-C cells decreased markedly and tended to remain constant after about eight cycles, i.e., after the bulk of the capacity loss.…”
Section: Cyclingsupporting
confidence: 86%
“…Most of the capacity fade at the 8-C rate occurred before eight cycles; after that, there was only a slight additional fade. With cycling, the variability in the measured values of capacity tended to increase in a manner consistent with that reported by Tanim et al [55] By contrast, the variability in the 8-C cells decreased markedly and tended to remain constant after about eight cycles, i.e., after the bulk of the capacity loss.…”
Section: Cyclingsupporting
confidence: 86%
“…Twenty‐four, single‐layer, xx3450 pouch cells (≈32 mAh) were made by the Cell Analysis, Modeling and Protoyping (CAMP) Facility at Argonne. [ 19 ] The electrodes in the cell measured 34 × 50 mm. The composition of the single‐sided electrode laminates is shown in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…[68] Optical Imaging/Microscopy: Owing to the ubiquitous nature of digital photography, optical imaging remains a very popular approach toward qualitatively recording the extent and heterogeneity of Li plating across the surface area of the anode. [6,72,[77][78][79] Imaging is referred to as pictures taken with a camera (such as cellphone camera), that does not have specialized focusing optics while microscopy explicitly uses focusing optics to furnish micrographs. Optical imaging is particularly effective in LIBs due to the distinct shiny nature of metallic Li contrasted against the dark graphite, which is a typically anode in LIBs, as well as the distinct colors of lithiated graphite species.…”
Section: Qualitative Surface-based Imagingmentioning
confidence: 99%
“…[85] Sagane et al observed the plating and stripping reactions of Li on a Cu substrate, while also noting the reactivity of the plated Li with any tiny amounts of oxygen and moisture in the SEM chamber, [22] as shown in Figure 6b. Tanim www.advancedsciencenews.com et al showed an increased C-rate resulting in a larger amount of plated Li, [6] while Honbo et al showed that defects on the graphitic anode surface suppressed the formation of Li dendrites. [86] Bieker et al used SEM to investigate the correlation between Li plating, SEI formation, and electrolyte decomposition at the Li metal anode surface.…”
Section: Qualitative Surface-based Imagingmentioning
confidence: 99%
See 1 more Smart Citation